Thematic Stagnation and Methodological Conservatism in Arabic Language Education Master’s Theses at Universitas Islam Negeri Sunan Kalijaga: A Mixed-Methods Content Analysis - Muhajir Muhajir; Muhammad Sya’dullah Fauzi; Abdulghani Sultan Alfakih (MyResearch ID Publishing, 2025)
Purpose – This study maps thematic stagnation and methodological conservatism in master’s theses in Arabic Language Education (PBA) at Universitas Islam Negeri Sunan Kalijaga (2015–2021) and the intellectual dynamics of topic–method choices to inform program evaluation and policy. Methods/Design/Approach – A descriptive design with a historical approach and a mixed-methods strategy was applied to the full corpus of 178 theses (total sampling, 2015–2021). Data were gathered via documentation/bibliographic survey of digital and physical archives and analysed using content analysis and frequency distributions (P = (F/N) × 100). The study complied with institutional research ethics and received ethics committee approval. Findings – Six themes were identified; teaching–learning components dominate 50% (89/178) with teaching materials as the largest subtheme 22.5% (40/178). Linguistics appears consistently yet remains minor 14.6%; educational technology 7.9% increased in 2019–2021, while maharah declined 4.5%. Methods are led by R&D 27.5% (49), activity analysis 24.7% (44), literature review 17.4% (31); experiments 5.6% (10) rose in the last two years. Originality/Value – Program-level thematic–methodological mapping pinpoints where stagnation occurs while signalling shifts (technology and experiments), guiding a move toward more explanatory, cross-level, and interdisciplinary designs grounded in a thematic lens attentive to diglossia. Practical Implications – Three operational steps are recommended: (i) redesign the research roadmap (applied sociolinguistics, policy/curriculum evaluation, multicultural agendas); (ii) strengthen methodological capability (causal/explanatory designs, mixed methods, program evaluation) to buttress R&D; (iii) orchestrate cross-disciplinary collaborations and field partnerships. Keywords Arabic Language Education (PBA), thesis mapping, research themes, research methods, Indonesia Paper type Research paper